A clinical study of Laryngo- tracheal stenosis - Mohammed Naveed Ahmed; M. Mahendra Kumar; S. Muneeruddin Ahmed; G. Shahul Hameed; G. Siva Prasad (Al Ameen Medical College, 2014)
Introduction: Laryngo-tracheal Stenosis is a common, complex problem resulting most often from intubation, direct trauma or autoimmune disease. Recently airway trauma has increased considerably owing to increased ventilator care in many emergencies. Objective of the Study: The aim of the present clinical study is to review the Aetiology, clinical features and indications of emergency tracheostomy to save life in patients who develop stenosis of the upper airway. The study also reviews the planned repair of the stenosed segment. The upper trachea and Sub-glottis are approached through a midline neck incision and stenosed segment is repaired with Montgomery 'T' tube stenting. Material and Methods: Twenty five patients attending Government General Hospital; Kurnool; India, presenting with airway obstruction following discharge after being treated in Emergency care ward were included in this study. A Montgomery 'T' tube was used in 23 patients, resection anastomoses in 1 patient and medical management in 1 patient was undertaken. All the patients were followed for 24 - 36 months with regular follow up. Post extubation radiological improvement. Results: The 'T' tube stenting was found to be ideal as it was cost effective, easy to perform under local anesthesia. There was no recurrence in any of the patients till the time of reporting.